2011
DOI: 10.1523/jneurosci.0910-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Phosphorylated TrkB Receptor in the Mouse Hippocampal Formation Depends on Sex and Estrous Cycle Stage

Abstract: TrkB is a neurotrophin receptor important for the synaptic plasticity underlying hippocampal-dependent learning and memory. Because this receptor is widely expressed in hippocampal neurons, the precise location of TrkB activation is likely important for its specific actions. The goal of this study was to identify the precise sites of TrkB activation in the mouse hippocampal formation, and to determine any changes in the distribution of activated TrkB under conditions of enhanced BDNF expression and hippocampal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
61
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 88 publications
9
61
0
Order By: Relevance
“…Indeed, quantification at low power (100×) in stratum radiatum of CA1 in the present study revealed no significant differences between NS and KA treated animals, despite robust increases following KA when pY816+ dendritic shafts and spines were quantified at high power (630×). These results are consistent with ultrastructural evidence localizing pY816 immunoreactivity to dendritic shafts of CA1 pyramids and a minority (5%) of spines within stratum radiatum of CA1 under basal conditions (Spencer-Segal et al, 2011); notably, activated TrkB was clustered next to the postsynaptic density. Light microscopic studies have also colocalized pTrkB immunoreactivity with a subset of PSD-95 (5%) in stratum radiatum of CA1, and the fraction of pTrkB colocalizing with PSD-95 increased approximately 2-fold following an unsupervised learning paradigm (Chen et al, 2010a;Chen et al, 2010b).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Indeed, quantification at low power (100×) in stratum radiatum of CA1 in the present study revealed no significant differences between NS and KA treated animals, despite robust increases following KA when pY816+ dendritic shafts and spines were quantified at high power (630×). These results are consistent with ultrastructural evidence localizing pY816 immunoreactivity to dendritic shafts of CA1 pyramids and a minority (5%) of spines within stratum radiatum of CA1 under basal conditions (Spencer-Segal et al, 2011); notably, activated TrkB was clustered next to the postsynaptic density. Light microscopic studies have also colocalized pTrkB immunoreactivity with a subset of PSD-95 (5%) in stratum radiatum of CA1, and the fraction of pTrkB colocalizing with PSD-95 increased approximately 2-fold following an unsupervised learning paradigm (Chen et al, 2010a;Chen et al, 2010b).…”
Section: Discussionsupporting
confidence: 89%
“…These results confirm earlier work that reported increased pTrkB immunoreactivity in stratum lucidum during epileptogenesis, yet was unable to identify the cellular structures containing this immunoreactivity (Binder et al, 1999a;He et al, 2004;He et al, 2002;He et al, 2010). The present results are also consistent with recent ultrastructural evidence localizing pY816 immunoreactivity to mossy fiber axons and a minority (5%) of boutons within SL under basal conditions (Spencer-Segal et al, 2011); pY816 immunoreactivity within boutons was most often affiliated with small synaptic vesicles opposite the synaptic contact.…”
Section: Discussionsupporting
confidence: 84%
“…[25,26] The distribution of phosphorylated TrkBs was found to be affected by estradiol levels. [27] However, the real mechanism of estrogen that influences TrkB protein is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…An electron microscopic study revealed that phosphorylated-TrkB (pTrkB), the activated form of TrkB, is localized primarily to axons and axon terminals, but is also present in dendritic shafts and spines of hippocampal neurons (202). There was also abundant pTrkB in microglial profiles identified using immunofluorescence and confocal microscopy.…”
Section: Estrogen Actions On Synapse Formation Across Speciesmentioning
confidence: 99%